Preparation of composite polymer electrolytes by electron beam-induced grafting : proton and lithium ion-conducting membranes - Nasef, M. M.; Saidi, H.; Dahlan, K. Z. M. (Elsevier, 2007)
Two classes of composite polymer electrolyte membranes, one conducting lithium ions (Li+) and the other conducting protons (H+) were prepared using simultaneous electron beam-induced grafting. Porous poly(vinylidene fluoride) (PVDF) films were impregnated with styrene and subjected to electron beam (EB) irradiation to obtain polystyrene (PS) filled PVDF precursor films that were subsequently treated with either chlorosulfonic acid/1,1,2,2-tetrachloroethane mixture to obtain H+-conducting composite membranes or LiPH6/EC/DEC liquid electrolyte to obtain Li+-conducting composite membranes. The properties of the obtained membranes were evaluated using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and AC impedance measurements. The obtained membranes were found to achieve grafting content up to 46% with superior Li+-conductivity of 1.91 Ã— 10-3 S/cm and H+-conductivity of 5.95 Ã— 10-2 S/cm. The results of this work show that simultaneous radiation-induced grafting with EB is a promising method to prepare high quality ion-conducting membranes for possible use in fuel cells and lithium batteries.